A.03 Cerebral perfusion and its relationship to post-concussion syndrome in mild traumatic brain injury: a prospective controlled cohort study. (17th June 2016) - Barlow, KM; Marcil, LD; Dewey, D; Carlson, H; MacMaster, FP; Brooks, BL; Lebel, RM
Abstract : Background: Persistent post-concussive symptoms (PCS) have been linked to increased cortical network activation and decreased cerebrovascular reactivity. Decreased cerebral perfusion could help explain PCS and may be a biomarker to track recovery.Methods: Children (ages 8 to 18 years) symptomatic with PCS at one month post-injury were studied. Children who recovered following a mTBI (asymptomatic group) and healthy children acted as controls. Pseudocontinuous arterial spin labeling MRI was used to quantify cerebral blood flow (CBF). All subjects were imaged at approximately 40 days post-injury. Symptomatic group underwent repeat neuroimaging 4-5 weeks later.Results: Seventy-two participants (14.1 years; 95% CIs: 13.5, 14.8) underwent neuroimaging at 40 days post-injury. Global CBF was significantly higher in the symptomatic group compared to healthy controls, and lower in the asymptomatic group (F(2, 57) 9.734 p<0.001). Symptomatic children had increased CBF in the frontal and occipital regions, and asymptomatic children had decreased CBF in the temporal regions compared to healthy controls. CBF decreased in symptomatic children over time. CBF was a predictor of cognition (R 2 =0.235;p=0.001).Conclusions: Cerebral perfusion is altered in children with mTBI and is associated with recovery trajectory. Asymptomatic children had decreased CBF suggesting cerebral recovery is ongoing. Further longitudinal studies are required to determine if these perfusion patterns continue to change over time.